The just world hypothesis and the attribution of agency to a victim - Gonzalez, Arthur E. John; Cordoza, Marian L.; Chapman, Matthew G. (The Greek Review of Social Research, 1976)
A study was designed to test the just world hypothesis in a situation where the derogation of an innocent victim was socially proscribed. In a 3 X 2 design, experimental subjects were asked to indicate their affect for an alleged victim of Nazi atrocities. In one condition, the victim supposedly received severe maltreatment. In the two remaining conditions, the severity of the maltreatment was either moderate or low. It was predicted that, contrary to the just world hypothesis, increased severity of maltreatment of the innocent victim would not result in his increased derogation. Rather, it was predicted that the restoration of justice would be realized by the attribution of increased agency of the victim in his suffering and decreased attribution to him as a victim of circumstance, as the severity of the suffering increased. The results supported the predictions, though the increased attribution of agency and decreased attribution of victimization by circumstance were found only in the case of extreme severity of maltreat ment.